Quantum Hall states observed in thin films of Dirac semimetal Cd3As2. Issue 1 (December 2017) - Uchida, Masaki; Nakazawa, Yusuke; Nishihaya, Shinichi; Akiba, Kazuto; Kriener, Markus; Kozuka, Yusuke; Miyake, Atsushi; Taguchi, Yasujiro; Tokunaga, Masashi; Nagaosa, Naoto; Tokura, Yoshinori; Kawasaki, Masashi
Abstract A well known semiconductor Cd3 As2 has reentered the spotlight due to its unique electronic structure and quantum transport phenomena as a topological Dirac semimetal. For elucidating and controlling its topological quantum state, high-quality Cd3 As2 thin films have been highly desired. Here we report the development of an elaborate growth technique of high-crystallinity and high-mobility Cd3 As2 films with controlled thicknesses and the observation of quantum Hall effect dependent on the film thickness. With decreasing the film thickness to 10 nm, the quantum Hall states exhibit variations such as a change in the spin degeneracy reflecting the Dirac dispersion with a large Fermi velocity. Details of the electronic structure including subband splitting and gap opening are identified from the quantum transport depending on the confinement thickness, suggesting the presence of a two-dimensional topological insulating phase. The demonstration of quantum Hall states in our high-quality Cd3 As2 films paves a road to study quantum transport and device application in topological Dirac semimetal and its derivative phases. Despite many achievements in the topological semimetal Cd3 As2, the high-quality Cd3 As2 films are still rare. Here, Uchida et al. grow high-crystallinity and high-mobility Cd3 As2 thin films and observe quantum Hall states dependent on the confinement thickness.